Analisis Kinerja Produksi Nilai Tambah dan Keuntungan Agroindustri Tempe di Kelurahan Kedamaian Kota Bandar Lampung - Divya Anggrainingsih; Dwi Haryono; Adia Nugraha (Politeknik Negeri Lampung, 2021)
This research aims to analyze the production performance, value added and profit of tempeh agroindustry. Respondents in this research were owners and employees of agroindustry. The method used is a case study on Mr. Zainal's tempe agroindustry in Kedamaian Village. This research was conducted in November 2021–December 2021 and the analytical method used was descriptive qualitative and quantitative. The results of this research showed that the production performance of tempe agroindustry in terms of quality, processing speed and delivery speed is good, but in terms of productivity and flexibility aspects are still not optimal. The value added of agroindustry is quite good because it shows that processing soybeans into tempe provides positive value added. The profit obtained by the agroindustry per production is Rp.1.081,418,92, the biggest profit comes from tempe products with size C